2013
DOI: 10.19026/ajfst.5.3134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lupine Flour on Baking Characteristics of Gluten Free Cookies

Abstract: Celiac Disease (CD) is an immune-mediated disease in genetically susceptible individuals caused by intolerance to gluten protein in some cereals, resulting in mucosal inflammation, which causes malabsorption. An effective treatment for CD is a gluten-free diet that excludes cereals containing gluten. One of the most desirable wheat products is the cookie, which is considered suitable for all ages due to its low manufacturing cost, convenience, long shelf life and good eating quality. Therefore, the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Spread ratio (Table ) was in the range of 6.1 to 6.6 and was not significantly different. Other studies incorporating raw pulses in gluten‐free cookies at 40% found a spread ratio ranging from 7.15 to 8.41 (Maghaydah et al., ; Okpala & Chinyelu, ; Yamsaengsung et al., ). Spread ratio is influenced by the water‐holding capacity of the flours used, which is affected by protein content.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Spread ratio (Table ) was in the range of 6.1 to 6.6 and was not significantly different. Other studies incorporating raw pulses in gluten‐free cookies at 40% found a spread ratio ranging from 7.15 to 8.41 (Maghaydah et al., ; Okpala & Chinyelu, ; Yamsaengsung et al., ). Spread ratio is influenced by the water‐holding capacity of the flours used, which is affected by protein content.…”
Section: Resultsmentioning
confidence: 98%
“…As total protein increases, spread ratio decreases, due to increased water‐holding, and hence high viscosity resulting in restriction of lateral flow. Other factors at play that may also influence water‐holding and spread are sugar granulation, and type of sugar (Doescher & Hoseney, ; Fuhr, ; Maghaydah et al., ; Yamsaengsung et al., ). Cookie hardness was not significantly different among treatments, likely because protein content in pinto bean flours was very similar (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lupine bean ( Lupineus albus ) can be used as a base in GF cookies owing to its high levels of proteins (36–52 g per 100 g), fibre (30–40 g per 100 g) and vitamins such as thiamine, riboflavin, niacin, folate and vitamin E . Cookies prepared with 50% lupine flour and 50% corn starch had a high sensory score by panellists and contained higher fibre and proteins than a control containing gluten.…”
Section: Strategies For Improving Nutritional Quality Of Gf Productsmentioning
confidence: 99%